Complete remission of gallbladder neuroendocrine carcinoma with liver metastasis by tislelizumab plus chemotherapy: a case report - Li, Huafei; Qiao, Jiaming; Kou, Xiaoxia; Wu, Cong; Liu, Huiying; Qiu, Jinrong (Frontiers in Oncology, 2024)
Background Gallbladder neuroendocrine carcinoma (GB-NEC) is an extremely rare cancer with a poor prognosis in the clinic. Although surgical resection remains the primary and preferred therapeutics, many patients are in a late stage and lose the opportunity for surgery. However, due to the extremely low morbidity, the specific treatment guidelines for GB-NEC have not been established. Case presentation A 52-year-old woman was admitted to our hospital with the chief complaint of “almost 1 month after palliative surgery for metastatic gallbladder carcinoma.” According to the results of pathological findings and imaging manifestations, the patient was diagnosed with GB-NEC with a clinical stage of pT3N1M1 (IVB). The patient then received tislelizumab plus EP chemotherapy (etoposide 100 mg + cisplatin 30 mg, d1–3) every 3 weeks for 8 cycles from 12 November, 2021, followed by maintenance therapy (tislelizumab alone) every 3 weeks until now. The tumor response was evaluated as complete remission since 13 February, 2023. As of the last follow-up, the patient remains alive, with no complaints of discomfort. Conclusions Gallbladder NEC has no specific symptoms, and the diagnosis is based on pathological and immunohistochemical results. The therapeutic course and efficacy of the case in this study indicates that the application of PD-1 inhibitor might be a feasible therapeutic option for GB-NEC. However, this potential strategy needs validation by further clinical studies in the future.